Analisis Materi Bahasan, Karakteristik Penyajian Dan Preferensi Kajian Dalam Kitab Parukunan Melayu Besar Karya Haji Abdurrasyid Banjar - Syarif Hidayatullah, Muhammad (INSTITUT AGAMA ISLAM TARBIYATUT THOLABAH LAMONGAN, INDONESIA, 2018)
Book of Parukunan Melayu Besar is one of the most popular Malay books by Banjar scholars besides the book Sabilal Muhtadin (Syekh Muhammad Arsyad al-Banjari) Parukunan Jamaluddin (Mufti Haji Jamaluddin bin Arsyad al-Banjari / Fatimah bint Abdul Wahab Bugis), Undang-undang Sultan Adam (The Compilation Team of UUSA) Asrar as-Shalah (Abdurrahman Shiddiq bin Muhammad 'Afif Banjar), Risalah Rasam Parukunan (Haji Abdurrahman bin Haji Muhammad Ali) and Mabadi' ilmu fiqih by Haji Muhammad Sarni Alabio. This paper aims to analyze the book of Parukunan Melayu Besar in terms of subject matter, presentation characteristics and study preferences. The results of the discussion show that the book of Parukunan Melayu Besar in terms of subject matter focuses on worship fiqh and a little inserted material on the science of monotheism (fardhu syahadat, nature 20 and the nature of the prophet). The presentation characteristics can be categorized as practical fiqh, beginner fiqh and introductory fiqh. Then the study preferences can be influenced by the situation and conditions when this book was written which in the end focuses on the study of worship fiqh rather than social interaction fiqh.